Oh, What a Tangled Web: Russian Hacking, Fake News, and the 2016 US Presidential Election. - Berghel, Hal (Computer (00189162), 2017)
The real story behind alleged foreign interference in our election isn’t that it occurred—any impact on the outcome from Russian hacking and trolling was minimal—but that we set the standard for such activity and have no one but ourselves to blame.